Book reviewed: Colombia: democracia y paz. Editor: Alfonso Monsalve Solorzano - Mira B., Paula Cristina; Muñoz F., Sergio B.; Saldarriaga M., Andrés E. (Estudios de Filosofía, 2005)
Book reviewed: Colombia: democracia y paz. Editor: Alfonso Monsalve Solorzano